PRESENTASI DIRI DALAM KOMUNIKASI GAY DENGAN LINGKUNGAN SEKITAR - Sari, Novita (Jurnal Insani, 2017)
The aim of this study is to find out how gay self-presentation among heterosexuals and among gays. The research method used is descriptive qualitative method. The informant in this research is 2 gay people and 2 heterosexual people.The results showed that the communication made by gay has different presentation on the front stage (in heterosexual circles) by displaying the male figure and on the back stage (among fellow Gay) by showing himself the real. But there are two different sides in the Gay itself. Boti as a woman and on the other hand, Gay who is positioned as a man is called Gadun.